Acute Cerebellitis with Parvovirus Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
An immunocompetent 5-year-old girl with acute cerebellitis associated with parvovirus B19 (PVB19) infection is reported from Nishi-Kobe Medical Center and Tokyo Medical University, Japan.